Protocol for a multicentre, parallel, randomised, controlled trial on the effect of sweeteners and sweetness enhancers on health, obesity and safety in overweight adults and children: the SWEET project. Issue 10 (12th October 2022) - Kjølbæk, Louise; Manios, Yannis; Blaak, Ellen E; Martínez, J. Alfredo; Feskens, Edith J M; Finlayson, Graham; Andersen, Sabina S H; Reppas, Kyriakos; Navas-Carretero, Santiago; Adam, Tanja C; Hodgkins, Charo E; del Álamo, Marta; et al.
Abstract : Introduction: The aim of this randomised controlled trial (RCT) is to investigate whether prolonged consumption of sweeteners and sweetness enhancers (S&SEs) within a healthy diet will improve weight loss maintenance and obesity-related risk factors and affect safety markers compared with sugar. Methods and analysis: SWEET (S&SEs: prolonged effects on health, obesity and safety) is a 1-year multicentre RCT including at least 330 adults with overweight (18–65 years, body mass index (BMI) >25 kg/m 2 ) and 40 children (6–12 years, BMI-for-age >85th percentile). In an initial 2-month period, adults will consume a low-energy diet with the aim to achieve ≥5% weight loss. Children are advised to consume a generally healthy diet to maintain body weight, thus reducing their BMI-for-age z-score. In the following 10 months, participants will be randomised to follow a healthy ad libitum diet with or without S&SE products. Clinical investigations are scheduled at baseline, after 2, 6 and 12 months. The primary outcomes are body weight for efficacy and gut microbiota composition (in relation to metabolic health) for safety, both in adults. Secondary outcomes include anthropometry, risk markers for type-2 diabetes and cardiovascular diseases, questionnaires including, for example, food preferences, craving and appetite and tests for allergenicity. Ethics and dissemination: The trial protocol has been approved by the following national ethical committees; The research ethics committees of the capital region (Denmark), approval code: H-19040679, The medical ethics committee of the University Hospital Maastricht and Maastricht University (the Netherlands), approval code: NL70977.068.19/METC19-056s, Research Ethics Committee of the University of Navarra (Spain), approval code: 2019.146 mod1, Research Ethics Committee of Harokopio University (Greece), approval code: 1810/18-06-2019. The trial will be conducted in accordance with the Declaration of Helsinki. Results will be published in international peer-reviewed scientific journals regardless of whether the findings are positive, negative or inconclusive. Trial registration number: NCT04226911 (Clinicaltrials.gov)